A new lacustrine ricefish from central Sulawesi, with a redescription of Oryzias marmoratus (Teleostei: Adrianichthyidae) - Kobayashi, Hirozumi; Mokodongan, Daniel F.; Horoiwa, Mizuki; Fujimoto, Shingo; Tanaka, Rieko; Masengi, Kawilarang W. A.; Yamahira, Kazunori (Ichthyological research, 2023)
Oryzias loxolepis , new species, is described from Lake Towuti in the Malili Lake system, central Sulawesi, Indonesia. Historically this new species has been confused with Oryzias marmoratus (Aurich 1935), which we redescribe. While both species share dark brown blotches on a grayish-brown trunk, O. loxolepis differs from O. marmoratus in having 11 abdominal vertebrae, 12 or 13 transverse scales, a shorter caudal peduncle, terminal mouth, reduced nuchal concavity, slanted trunk scales, and a rounded male dorsal fin. Oryzias loxolepis can be also distinguished from Oryzias profundicola Kottelat 1990, another sympatric congener in Lake Towuti, in having a longer snout in both sexes, in males in having a larger head and eyes, and a black margined dorsal fin, and in females in having a shallower body depth at the anal- and dorsal-fin origins. A phylogenetic analysis based on genome-wide single nucleotide variants reveals O. loxolepis to be a sister taxon to O. profundicola rather than O. marmoratus . The identities of specimens historically referred to “ O. marmoratus ” in previous genetic studies are re-evaluated.